Disposition kinetics of ampicillin in buffalo calves - ALAM, M; BANERJEE, N C; YADAVA, K P (The Indian Journal of Animal Sciences, 2013)
The pharmacokinetics of ampicillin after single oral dose (20 mg/kg b w) was studied in group of buffalo calves. The highest mean plasma concentration of drug (0,44 ± 0,08 ug/ml) was recorded at 4 hr which declined gradually to 0.18 ± 0,01 ug/ml at 24 hr of drug administration. The mean ep therranged. from 0.18 ±0.01 to 0.44 ± 0.08. mg/ml between '30 min and 24 hr. The mean values of kine tie parameters for t1/2 ka, t1/2 beta, Vd area, AUC, CLB, T/P ratio were 1.14 ± 0.12 hr, 15.71 ± 1.19 hr, 39.11 ± 1.64 L/kg, 11.53 ± 0.61 mg/ml hr, 29.31 ± 1.66 ml/kg/min and 0.70 ± 0.04 respectively. The mean values of K12, K21 Kel, K12 and K21 were 0.23 ± 0.03/hr, 0.37 ± 0.03/hr, 0.07 ± 0.007/hr and 0.61 ± 0.04 respectively. Dosage regimen based on the drug kinetics has been suggested for optimal clinical efficacy.